INDIVIDUAL ACCOUNTABILITY IN COOPERATIVE LEARNING: MORE OPPORTUNITIES TO PRODUCE SPOKEN ENGLISH - Astuti, Puji; Lammers, Jayne C. (Indonesian Journal of Applied Linguistics, 2017)
The contribution of cooperative learning (CL) in promoting second and foreign language learning has been widely acknowledged. Little scholarly attention, however, has been given to revealing how this teaching method works and promotes learners’ improved communicative competence. This qualitative case study explores the important role that individual accountability in CL plays in giving English as a Foreign Language (EFL) learners in Indonesia the opportunity to use the target language of English. While individual accountability is a principle of and one of the activities in CL, it is currently under studied, thus little is known about how it enhances EFL learning. This study aims to address this gap by conducting a constructivist grounded theory analysis on participant observation, in-depth interview, and document analysis data drawn from two secondary school EFL teachers, 77 students in the observed classrooms, and four focal students. The analysis shows that through individual accountability in CL, the EFL learners had opportunities to use the target language, which may have contributed to the attainment of communicative competence—the goal of the EFL instruction. More specifically, compared to the use of conventional group work in the observed classrooms, through the activities of individual accountability in CL, i.e., performances and peer interaction, the EFL learners had more opportunities to use spoken English. The present study recommends that teachers, especially those new to CL, follow the preset procedure of selected CL instructional strategies or structures in order to recognize the activities within individual accountability in CL and understand how these activities benefit students.